Membrane fouling by organic macromolecules - Lau, Lei Fong. (2009)
Fouling of nanofiltration (NF) membrane by humic acid and natural organic matters (NOM) has been extensively investigated. The performance of NF membrane is a function of hydrodynamic condition (flux, applied pressure, cross-flow velocity) and chemical composition (pH, ionic strength, divalent ions). Optimize hydrodynamic condition was investigated to improve NF membrane performance and reduction in fouling tendency. The effect of hydrodynamic condition to the fouling of NF270 was extensively investigated with the used of Bovine Serum Albumin (BSA) as foulant. Cross-flow test unit was used in this experiment. The baseline conditions of this investigation were selected at 20mg/L BSA, 0.01M (mol/L) of ionic strength, at room temperature 20oC. Cross-flow velocity and initial flux were adjusted at different value. Flux decline rate was observed through the data logger while the amount of BSA deposited on NF270 membrane surface was measured by using UV absorbance method. The results of the fouling experiment indicated that (i) better membrane permeability was achieved at high applied pressure, (ii) significant fouling occurs at high initial flux which was greater than critical flux, and (iii) rapid build up of concentration polarization layer and cake layer at low cross-flow velocity. Such observations agreed well that the interaction between BSA-deposited-BSA was more prominent than the interaction between BSA-membrane. The BSA-deposited-BSA interaction is dependent on the drag force and electrostatic repulsion force among BSA molecules.